2020
DOI: 10.1186/s12870-020-02581-3
|View full text |Cite
|
Sign up to set email alerts
|

Activities of leaf and spike carbohydrate-metabolic and antioxidant enzymes are linked with yield performance in three spring wheat genotypes grown under well-watered and drought conditions

Abstract: Background: To improve our understanding about the physiological mechanism of grain yield reduction at anthesis, three spring wheat genotypes [L 1 (advanced line), L 2 (Vorobey) and L 3 (Punjab-11)] having contrasting yield potential under drought in field were investigated under controlled greenhouse conditions, drought stress was imposed at anthesis stage by withholding irrigation until all plant available water was depleted, while wellwatered control plants were kept at 95% pot water holding capacity. Resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 101 publications
3
52
0
Order By: Relevance
“…The level of wheat phytohormones in leaves and spikes was examined further to understand the mechanism of yield reduction. We found an increase in ABA concentration under elevated CO 2 both in leaf and spike, and similar results were reported in recent studies (Shokat, Großkinsky, et al, 2020). In general, we measured an increase in the concentrations of most of the phytohormones under drought conditions for both ambient and elevated CO 2 and a negative correlation of ACC, I3A and most of the CKs with An, Gs and yield‐related traits were noticed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The level of wheat phytohormones in leaves and spikes was examined further to understand the mechanism of yield reduction. We found an increase in ABA concentration under elevated CO 2 both in leaf and spike, and similar results were reported in recent studies (Shokat, Großkinsky, et al, 2020). In general, we measured an increase in the concentrations of most of the phytohormones under drought conditions for both ambient and elevated CO 2 and a negative correlation of ACC, I3A and most of the CKs with An, Gs and yield‐related traits were noticed.…”
Section: Discussionsupporting
confidence: 92%
“…Drought stress at anthesis interferes with normal floral development and lowers seed setting and grain filling in wheat and other crops (Ahmadi & Baker, 2001; Dong et al., 2017; Prasad, Pisipati, Momčilović, & Ristic, 2011; Razzaghi, Bahadori‐Ghasroldashti, Henriksen, Sepaskhah, & Jacobsen, 2020; Shokat, Großkinsky, Roitsch, & Liu, 2020; Shokat, Sehgal, Vikram, Liu, & Singh, 2020). Seed set is mainly reduced through lower water availability at meiosis causing malfunctioning of pollen grains (Dong et al., 2017; Westgate, Passioura, & Munns, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…As evident from Fig 1, Yd was very close to WUE confirming the results of correlation analysis. Previous reports indicate that higher Phr helps plants to maintain optimum grain yield as well as adaptability (Shokat et al, 2020b(Shokat et al, , 2021). In the current study, Phr was clustered closer to WUE and Yd (Fig.2) indicating maintenance of Yd could be due to higher WUE and Phr.…”
Section: Resultsmentioning
confidence: 99%
“…Many GST genes have been reported to play central roles in protecting plants from abiotic and biotic stress [ 19 , 46 48 ]; therefore, they are potential targets for crop breeding and improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Many GST genes have been reported to play central roles in protecting plants from abiotic and biotic stress [19,[46][47][48]; In this study, we identified a total of 346 GST genes in hexaploid common wheat (T. aestivum), 226 in tetraploid durum wheat (T. durum), 104 in diploid T. urartu, and 105 in diploid Ae. tauschii, using a comprehensive genomewide approach.…”
Section: Discussionmentioning
confidence: 99%